Developing a Mini Bilingual Encyclopedia of Ethnic Cuisine in East Java - Salsabila Farahdiba Arofah (UPT P2M Politeknik Negeri Malang, 2021)
In this study, the author uses the DDR research design from Richey and Klein 2013 because it focuses on the development and validation of a product so that it is very relevant to the research conducted by the author. This research design involves five stages: analysis, design, development, implementation, and evaluation. As well as in this study, the authors used interviews, questionnaires, and observation. The result of this research is a mini bilingual encyclopedia of ethnic cuisines in East Java which contains 25 kinds of ethnic cuisines in 17 cities/districts in East Java. The contents of the encyclopedia include an introduction, a guide to using the encyclopedia, a table of contents, a bibliography, a brief description and geographic map of East Java, and a description of each ethnic cuisine, including (name, origin, history, main ingredient, shop), pictures of each cuisine, and QR code feature that can directly connect to the YouTube that shows additional information about ethnic cuisines. This product is available in two languages, Indonesian and English, so that young Indonesians and foreigners/international students can access this product. The final result is that the mini bilingual encyclopedia of ethnic cuisines in East Java is presented in two versions, namely the printed encyclopedia and e-book, making it easy for the respondents to access this encyclopedia effectively according to their wishes. Therefore, this product received positive responses from various respondents regarding the quality of the encyclopedia, which has greatly helped them in getting to know the ethnic cuisines in East Java.